Waste Management Policies are being implemented in Tondo Village, Mantikulore District, Palu City - Rachmad; Gita Parista; Nuraisya (Journal of Public Administration and Government, 2022)
The purpose of this research is to examine how waste management rules are implemented in Tondo Village, Mantikulore District, Palu City. In this study, qualitative research methodologies were used to parse the data descriptively. Data was collected by observation, interviews, documentation, and data analysis utilizing descriptive analysis approaches. According to the study's findings, the implementation of waste management policies in Tondo Village, Mantikulore District, Palu City is still suboptimal, owing to the failure to apply the SOP. The waste problem has not been solved by resources. There are no waste management experts among human resources, which has an impact on policy implementation performance. Operational expenses are still inadequate, thus they must be included in order to accomplish the goals of Palu City's waste management strategy. Waste management facilities and infrastructure are still insufficient, resulting in a low level of management services. In terms of waste management implementation, officials must raise their socialization in program implementation, improve the quality of the implementing apparatus' resources, and offer suitable facilities so that trash management in Tondo Village may function smoothly.